Peripheral T cell lymphopenia in COVID-19: potential mechanisms and impact. Issue 1 (2nd July 2021) - Zhang, Sifan; Asquith, Becca; Szydlo, Richard; Tregoning, John S; Pollock, Katrina M
Summary: Immunopathogenesis involving T lymphocytes, which play a key role in defence against viral infection, could contribute to the spectrum of COVID-19 disease and provide an avenue for treatment. To address this question, a review of clinical observational studies and autopsy data in English and Chinese languages was conducted with a search of registered clinical trials. Peripheral lymphopenia affecting CD4 and CD8 T cells was a striking feature of severe COVID-19 compared with non-severe disease. Autopsy data demonstrated infiltration of T cells into organs, particularly the lung. Seventy-four clinical trials are on-going that could target T cell-related pathogenesis, particularly IL-6 pathways. SARS-CoV-2 infection interrupts T cell circulation in patients with severe COVID-19. This could be due to redistribution of T cells into infected organs, activation induced exhaustion, apoptosis, or pyroptosis. Measuring T cell dynamics during COVID-19 will inform clinical risk-stratification of hospitalised patients and could identify those who would benefit most from treatments that target T cells. Graphical Abstract: